A Laravel-Powered Web Application for Streamlining Medical Device Management at Prima Medika Hospital - Putu Adi Guna Permana; Pande Putu Gede Pratama; Anak Agung Manik Artawan (Telkom University, 2026)
Prima Medika Hospital utilizes a wide range of medical equipment, from basic diagnostic tools toadvanced technology devices. Effective management is essential to ensure the safety and functionalityof these medical tools for both patients and hospital staff. However, the hospital's current informationsystem does not fully comply with accreditation standards, highlighting the need for improvement.This study focuses on designing and developing a web-based medical equipment managementinformation system that streamlines processes such as procurement, inventory tracking, monitoring,maintenance, repairs, calibration, and recalls. The system is built using PHP with the Laravelframework, following the waterfall development methodology. Key design models include Data FlowDiagram (DFD) for data process visualization, Entity-Relationship Diagram (ERD) for databasestructuring, and interface design for user experience optimization. The system development andtesting environment utilize LARAGON, ensuring a stable and efficient local server setup. Systemtesting using the Blackbox method confirms that the platform operates as required. Additionally, UserAcceptance Testing (UAT) with 10 respondents indicates a user satisfaction rate of 92.3%,demonstrating a high level of effectiveness and usability